The Anatomical Distribution of Mechanoreceptors in Mouse Hind Paw Skin and the Influence of Integrin α1β1 on Meissner-Like Corpuscle Density in the Footpads - Wai, Valerie; Roberts, Lauren; Michaud, Jana; Bent, Leah R.; Clark, Andrea L. (Frontiers in Neuroanatomy, 2021)
Afferent neurons and their mechanoreceptors provide critical sensory feedback for gait. The anatomical distribution and density of afferents and mechanoreceptors influences sensory feedback, as does mechanoreceptor function. Electrophysiological studies of hind paw skin reveal the different types of afferent responses and their receptive fields, however the anatomical distribution of mechanoreceptor endings is unknown. In addition, the role of integrin α1β1 in mechanoreceptor function is unclear, though it is expressed by keratinocytes in the stratum basale where it is likely involved in a variety of mechanotransduction pathways and ion channel functionalities. For example, it has been shown that integrin α1β1 is necessary for the function of TRPV4 that is highly expressed by afferent units. The purpose of this study therefore was to determine and compare the distribution of mechanoreceptors across the hind paw skin and the footfall patterns of itga1-null and wild type mice. The itga1-null mouse is lacking the integrin α1 subunit, which binds exclusively to the β1 subunit, thus rendering integrin α1β1 nonfunctional while leaving the numerous other pairings of the β1 subunit undisturbed. Intact hind paws were processed, serially sectioned and stained to visualize mechanoreceptors. Footfall patterns were analyzed as a first step in correlating mechanoreceptor distribution and functionality. Merkel cells and Meissner-like corpuscles were present, however Ruffini endings and Pacinian corpuscles were not observed. Meissner-like corpuscles were located exclusively in the glabrous skin of the footpads and digit tips, however Merkel cells were found throughout hairy and glabrous skin. The increased density of Merkel cells and Meissner-like corpuscles in footpads 1, 3 and Meissner-like corpuscles in footpad 4 suggests their role in anteroposterior balance, while Meissner-like corpuscle concentrations in digits 2 and 5 support their role in mediolateral balance. Finally, a larger density of Meissner-like corpuscles in footpads 3 and 4 in male itga1-null mice compared to wild type controls paves the way for future site specific single fiber in vivo recordings to provide insight into the role of integrin α1β1 in tactile mechanotransduction.